Bendix Corporation Model MA-011 Variable Oscillator - Bendix Corporation (1970)
General view of a Bendix Corporation MA-011 Variable Oscillator designed for use with a Bendix Time-of-Flight Mass Spectrometer. The Time-of-Flight Mass Spectrometer (TOFMS) was the flagship analytical instrument of the Bendix Corporation.
Keywords: Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation